Understanding Fluid–Rock Interactions and Lixiviant/Oxidant Behaviour for the In-situ Recovery of Metals from Deep Ore Bodies - Hidalgo Rosero, Tania Marcela (Curtin University, 2020)
This research aimed to understand the fluid–rock interactions that may occur during the in-situ recovery of metals from deep ore bodies. Lixiviant/oxidant solution efficiencies were compared based on copper dissolution from copper sulfides under set conditions. Leach performance was evaluated based on fluid chemical analysis and solids morphological and compositional changes after interaction with the fluids and included studies on acid- and oxidant-depleted environments, composite sample kinetics and multi-stage contact between rock and fluid.